AUDIT KEAMANAN SISTEM INFORMASI PERUSAHAAN DENGAN KERANGKA KERJA COBIT 4.1 - Laela Kurniawati (Paradigma, 2013)
Demand for the audit of information systems (IS) in line with the greater complexity of the SI itselfcan be seen from all areas operating system, database, application, infrastructure (LAN, WAN), tothe model management (outsourcing / insourcing) is increasingly diverse. SI audit initially servesas a support function of a financial audit. This has become a necessity which is now almost allfinancial transactions are computerized. Of functions to support the financial audit, audit SI thendeepened by specializing in the implementation and evaluation of existing controls on SI purposeis to protect information assets and ensure that controls are effective in the process ofcomputerization. Issues to be discussed in this study is whether the security system in particular,the existing information on the company is good for the memastikn hl informsi system audit will beconducted that focuses on the security system, how the audit of information systems (IS) /information technology (IT) will be done keragka work with COBIT.Keywords: Information Systems, Information Systems Audit, COBIT